Parental perception of stress and emotional-behavioural difficulties of children with autism spectrum disorder and specific language impairment. (October 2020) - Di Renzo, Magda; Bianchi di Castelbianco, Federico; Vanadia, Elena; Petrillo, Massimiliano; Racinaro, Lidia; Rea, Monica
Background and aims: The daily challenges of caring for a child with autism spectrum disorder affect many areas of everyday life and parental well-being, as well as parents' ability to manage the needs of the family and the child concerned. A better understanding of parents' perception of their child's characteristics can allow better support for them and individualize intervention protocols in a more accurate way. The main objective of this study is the evaluation of the perception of stress by parents of children with autism compared to parents of children with specific language impairment. Methods: The parents of 87 children aged between 2 and 6 years were included in this study, 34 children with a specific language impairment diagnosis and 53 children with an autism spectrum disorder diagnosis (ASD) or at risk of developing it. They were asked to complete a self-report on perceived stress and rating scales on adaptive/problematic behaviours, executive functions and sensory profile of the child. Results: The results reveal that parents of ASD children, compared to the control group, showed significantly higher levels of stress, mainly due to the difficulty of managing unexpected events, the feeling of loss of control over one's life and the fear of not being able to cope with the adversities they were experiences. The most critical area, both for ASD and control group, concern the executive function related to emotional reactions. Conclusions: Thus, we argue that the difficulties in self-control, sensory modulation and emotional regulation, represent an element of stress for parents of children with developmental disorders. Implications: Regarding the difficulties of children with ASD, supporting the ways in which caregivers adapt to the signals of children is an important strategy, which has now become a key element of treatments for autism mediated by parents.